Changes in developmental assets across a 4-month competitive season among youth basketball players - Felipe G Mendes; André L A Soares; Ahlan B Lima; Carlos E Palheta; Luisa D Kós; Fabricio João Milan; Carine Collet; Humberto M Carvalho (Universidade Federal de Santa Catarina, 2019)
The present study examined the changes in developmental assets among young basketball players during a 4-month competitive period, accounting for variation by age group. Additionally, we examined the age-related variation on developmental assets. Sixty-five adolescent basketball players aged between 9.5 to 17.3 years were considered. We used the Portuguese version of the Developmental Assets Profile Questionnaire. Multilevel modeling was used to estimate the magnitude of changes on developmental assets across the 4-month competitive season, as well as aligning assets scores by chronological age. Positive values and positive identity scores were substantially increased after the 4-month competitive sample. The other assets scores showed no variation across the competitive 4-month competitive season, independent of age group. There was a trend of linear decrease in developmental assets as the adolescent players got older. For positive values, there was a non-linear trend with a higher decrease rate between about 10 to 14 years, levelling off thereafter. Developmental assets did not appear to be influenced by exposure to a period of organized training and competition among adolescent basketball players. Hence, the observed decrease on developmental assets when aligning by age may reflect the influence of contextual and cultural environments of practice. This is of particularly interest for positive values, which refer to school engagement or and social justice, qualities that are not sport-specific but assume a key and importance position in sport participation for a positive role in youth development.